Extension of Endocardium-Derived Vessels Generate Coronary Arteries in Neonates. Issue 3 (4th February 2022) - Tang, Juan; Zhu, Huan; Tian, Xueying; Wang, Haixiao; Liu, Shaoyan; Liu, Kuo; Zhao, Huan; He, Lingjuan; Huang, Xiuzhen; Feng, Zhao; Ding, Zhangheng; Long, Ben; et al.
Abstract : Background: Unraveling how new coronary arteries develop may provide critical information for establishing novel therapeutic approaches to treating ischemic cardiac diseases. There are 2 distinct coronary vascular populations derived from different origins in the developing heart. Understanding the formation of coronary arteries may provide insights into new ways of promoting coronary artery formation after myocardial infarction. Methods: To understand how intramyocardial coronary arteries are generated to connect these 2 coronary vascular populations, we combined genetic lineage tracing, light sheet microscopy, fluorescence micro-optical sectioning tomography, and tissue-specific gene knockout approaches to understand their cellular and molecular mechanisms. Results: We show that a subset of intramyocardial coronary arteries form by angiogenic extension of endocardium-derived vascular tunnels in the neonatal heart. Three-dimensional whole-mount fluorescence imaging showed that these endocardium-derived vascular tunnels or tubes adopt an arterial fate in neonates. Mechanistically, we implicate Mettl3 (methyltransferase-like protein 3) and Notch signaling in regulating endocardium-derived intramyocardial coronary artery formation. Functionally, these intramyocardial arteries persist into adulthood and play a protective role after myocardial infarction. Conclusions: A subset of intramyocardial coronary arteries form by extension of endocardium-derived vascular tunnels in the neonatal heart. Abstract : Supplemental Digital Content is available in the text.